Greenland, view of Kjerulf Fjord through to Dicksons Fjord - Boyd, Louise Arner, 1887-1972 (1931)
August 2, 1931. Kjerulfs [Kjerulf] Fjord. Through to Dickson [Dicksons] Fjord. In background; mountains forming eastern side of Kjerulfs [Kjerulf] Fjord; here seen at the extreme inner end of the fjord, at the NE end of Main Valley. In foreground; floor of Main Valley. Looking E.N.E.